Racial differences in psychosocial resources and mental and physical health outcomes during pregnancy: a structural equation modeling approach - Charlotte V. Farewell; Sarah J. Schmiege; Jenn A. Leiferman (Maternal Health, Neonatology and Perinatology)
Abstract Objectives Poor prenatal health is of particular concern among minoritized individuals who may experience adverse social determinants of health contributing to the intergenerational transmission of health disparities. The purpose of this study was to investigate associations between psychosocial resources, and mental and physical health among a prenatal sample, and to explore if these relationships vary by race. Methods English-speaking pregnant individuals living in the United States were recruited using Centiment (n = 340). Participants completed a 121-item cross-sectional survey. We conducted a single- and multi-group structural equation model to test hypothesized relationships, and then investigated differences by pregnant White individuals versus Black, Indigenous, and People of Color (BIPOC). Results Our final single-group model exhibited good model fit (χ2 (43) = 99.07, p < .01, CFI = 0.97, SRMR = 0.04, and RMSEA = 0. 06 (0.05—0.08)). After controlling for demographic characteristics and social determinants of health, higher levels of mindfulness were statistically significantly related to lower anxiety and depression scores (both p < .01). Higher levels of social supports were statistically significantly related to lower anxiety scores. Scale measurement invariance was confirmed for the multi-group model and the structural model was statistically significantly different between pregnant White individuals and BIPOC in this sample (Δ χ2 (27) = 116.71, p < .01). Conclusions Identification of core components of psychosocial resource interventions, consideration of upstream structural determinants, mindfulness and valued-living (MVL)-based strategies, cultural adaptation, and an emphasis on resilience rather than psychopathology may result in improved prenatal health among pregnant individuals traditionally underrepresented in research.